KEPERCAYAAN DIRI ANAK ASUH PADA PANTI ASUHAN PUTERI AISYIYAH KELURAHAN KAMPUNG MELAYU SUKAJADI PEKANBARU - Sari, Mila Kurnia; ayub, Daeng; Irja, Desti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: How high is foster child confidence in the Puteri Aisyiyah orphanage in Kampung Melayu Village of Sukajadi Pekanbaru, is there a variation in the level of foster child confidence based on education level, age, origin and status, how contributing aspects of foster care trust in the Puteri Orphanage Aisyiyah Kelurahan Kampung Melayu Sukajadi Pekanbaru. This research is descriptive with a quantitative approach. The population in this study consisted of 33 people. Sampling in this study uses saturated sampling. The instrument used was a questionnaire with 37 article overviews. The confidence of foster children in the Puteri Aisyiyah Orphanage Kampung Melayu Village Sukajadi Pekanbaru was measured by indicators (1) confidence in their own abilities, (2) optimism, (3) goal, (4) tolerance, (4) responsibility, (6) rational. From the results of the study it is known that (1) The level of trust of foster children in the Puteri Aisyiyah orphanage Kampung Melayu Village Sukajadi Pekanbaru is of a high interpretation. (2) Analysis of differences in the confidence of foster children on the basis of education level, age, origin and status, it is clear that the confidence of foster children varies considerably on the basis of education level and regional origin, on the basis of age and the status of absence of variation. significant. (4) Aspects that make the greatest contribution to the self-confidence of foster children are number 5 aspects, which are responsible in comparison with the SCRO (81.10%), which is classified as high in relation to the other aspects.Key Words: Trust, Foster children